(untitled) (Journal of Finance, Business and Management Studies, 2022)
The outbreak of the COVID-19 was declared a pandemic by the World Health Organization during their virtual press conference on 11 March 2020. The event can be termed a ’Black Swan’ because of its low probability and devastating impact on all sectors of the economy. Maritime Transport that accounts for 80% - 90% of the world trade, also witnessed the unprecedented impact. The paper examines the maritime transport industry during the COVID 19 pandemic. The maritime transport performance of 12 Asian countries has been analyzed. The data set has been collected for the period spanning from January 2018 to June 2021 from the United Nations Conference on Trade and Development (UNCTAD) website to measure Maritime Transport’s performance during the COVID-19 pandemic. The findings reveal that the indicators - port calls, median time spent in ports and liner shipping connectivity was affected due to the COVID-19 pandemic.